Women, water and memory : recasting lives in Palestine - Naguib, Nefissa, 1960- (Women and Gender: The Middle East and the Islamic World, 2009)
This book tells a different story about water. Against the backdrop of the end of the Ottoman Empire to the Palestinian uprisings, old Palestinian women recount life before and after piped water. While talking about fetching and managing household water, women also talked about being women. Women, Water and Memory speaks of many different lives. We hear stories about women's own strength and beauty, and about the woman who married a man whose ugly face made her sick. While one woman married the man "she cared for", another was relieved that her husband died when she was too old to be forced to remarry. We learn about the joy they feel each time they dance at a wedding, the sheer satisfaction of lighting a cigarette, the loyalty and shared despair towards families with members in prison, and about the tears of sorrow at each death and the delight at each birth.